2017
DOI: 10.18203/2349-3291.ijcp20172023
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological factors and clinical profile of neonatal jaundice from a rural area of North Kerala, India

Abstract: Background: Neonatal jaundice is the most common problem in the first week of life leading to delayed hospital discharge and readmissions. Early recognition of neonatal hyperbilirubinemia is important to prevent serious complications. This study was done in a teaching hospital (KMCT Medical College, Mukkam, Kozhikode), in a rural area of North Kerala. It is an attempt to identify the common aetiological factors of neonatal jaundice in this setting.Methods: This observational study was conducted over a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…G6PD deficiency was reported in 2.6% neonates by Merchant et al [12] and 3.4% by Narang et al [7] , where as in our study, no case of G6PD was observed. In study conducted by Shemeena Valiyat et al [15] out of 110 jaundiced neonates, 102 (92.5%) were term babies and 8 (7.3%) were preterm, 69 (62.75%) were males and 41 (37.27%) females. Physiological jaundice was seen in 44 (40%) of neonates.…”
Section: Discussionmentioning
confidence: 96%
“…G6PD deficiency was reported in 2.6% neonates by Merchant et al [12] and 3.4% by Narang et al [7] , where as in our study, no case of G6PD was observed. In study conducted by Shemeena Valiyat et al [15] out of 110 jaundiced neonates, 102 (92.5%) were term babies and 8 (7.3%) were preterm, 69 (62.75%) were males and 41 (37.27%) females. Physiological jaundice was seen in 44 (40%) of neonates.…”
Section: Discussionmentioning
confidence: 96%
“…Which of these n e o n a t e s w i l l e x p e r i e n c e s u b s t a n t i a l hyperbilirubinemia (Total Serum Bilirubin 15mg/dl) is difficult to predict. 3% of normal-term newborns 7,8 often have significant hyperbilirubinemia. Non-invasive, most affordable, and feasible investigation at delivery is an estimation of umbilical cord blood bilirubin (UCB).…”
Section: Diagnostic Accuracy Of Cord Blood Bilirubin In Predicting Ne...mentioning
confidence: 99%